The #MeToo effect : what happens when we believe women - Gilmore, Leigh, 1959- (Columbia University Press, 2023)
"The #MeToo movement gained widespread recognition in October 2017 as a direct response to the sexual assault allegations leveled at Harvey Weinstein but, more broadly, the movement exposed the systemic practice of doubting women's testimonies and denying accountability for their harassers. In this book Gilmore explains how the movement gained traction. It was a phenomenon based on storytelling and was, importantly, collective, raising awareness about sexual abuse through what Gilmore terms "narrative activism." While the courts are notorious for failing survivors of sexual violence, Gilmore argues that "narrative testimony rebalances the cultural conversation away from law, where survivors are structurally unequal to those who abuse them, toward life writing, where they have greater flexibility in telling their stories." In other words, the movement disrupted the mainstream conversation that often discredits women's testimony, instead creating a "collective witness" to women's experiences with sexual violence that shows the failings of civil and criminal procedures for dealing with sexual abuse. Gilmore offers an account of the political and cultural events that led up to and laid the groundwork for #MeToo and its explosion of collective testimony. She says that the emergence of #MeToo in 2017 was a breakthrough, but also a continuation of a long struggle dating back to Black women's antirape activism in slave narratives. She makes a strong case for the long legacy of narrative activism. She provides readings of all narrative forms that "filled the public square as resurgent testimony.""-- Provided by publisher
Keywords: MeToo movement.; Sexual harassment of women.; Women -- Crimes against.; Mouvement #MoiAussi.; Harcèlement sexuel.; Femmes -- Crimes contre.; SOCIAL SCIENCE / Activism & Social Justice; MeToo movement; Sexual harassment of women; Women -- Crimes against; Electronic books.